Freeze-Drying Chlorella vulgaris by Using Aquafaba, Deactivated Yeast, Inulin and Maltodextrin - Tamturk, Faruk; Gurbuz, Basak; Dalabasmaz, Sevim; Durmaz, Yasar; Konar, Nevzat; Toker, Omer Said; Karimidastjerd, Atefeh (WILEY, 2026)
The effects of novel wall materials for Chlorella vulgaris were reported using spray-drying in our previous study. In this study, we extend this work by applying freeze-drying, another major and widely used encapsulation technique, and encapsulate C. vulgaris biomass using this method. The experimental design was prepared using the Simplex-Lattice Mixture Design method. The independent variables were combinations of various wall materials such as maltodextrin (18-20 DE), inulin (DP < 10), aquafaba, and deactivated yeast as spray-dried Saccharomyces cerevisiae cells (25.0%-75.0%, w/w, in dm) and C. vulgaris biomass (25.00%-100.0%, w/w, in dm). The amounts of pigments, crude protein, physicochemical and color properties, wettability, hygroscopicity, and drying and encapsulation efficiency of the samples were determined. Significant models (p < 0.05) for moisture (1.30-3.36 g/100 g), total carotenoid (0.36-1.62 mg/g), total chlorophylls (8.51-29.8 mg/g), and crude protein (6.40-43.8 g/100 g) contents were obtained. Furthermore, it was found that the size and coalescence trends of the samples were influenced by the maltodextrin ratio used. Based on the results of this study, innovative materials such as deactivated yeast and aquafaba have significant potential for use in microalgae encapsulation and drying.
Keywords: Chlorella vulgaris; encapsulation efficiency; microalgae preservation; microencapsulation; WALL MATERIAL; EXTRACTION; FOOD; ENCAPSULATION; CAROTENOIDS; PROTEINS; BIOMASS; Food Science & Technology